Common Genetic Variation in GLP1R and Insulin Secretion in Response to Exogenous GLP-1 in Nondiabetic Subjects: A pilot study - Sathananthan, Airani (American Diabetes Association, 2010)
OBJECTIVE: Glucagon-like peptide (GLP)-1 receptor is encoded by GLP1R. The effect of genetic variation at this locus on the response to GLP-1 is unknown. This study assessed the effect of GLP1R polymorphisms on insulin secretion in response to hyperglycemia and to infused GLP-1 in nondiabetic subjects. RESEARCH DESIGN AND METHODS: Eighty-eight healthy individuals (aged 26.3 ± 0.6 years, fasting glucose 4.83 ± 0.04 mmol/l) were studied using a hyperglycemic clamp. GLP-1 was infused for the last 2 h of the study (0.75 pmol/kg/min over 121–180 min, 1.5 pmol/kg/min over 181–240 min). β-Cell responsivity (Φ(Total)) was measured using a C-peptide minimal model. The effect of 21 tag single nucleotide polymorphisms (SNPs) in GLP1R on Φ(Total) was examined. RESULTS: Two SNPs (rs6923761 and rs3765467) were nominally associated with altered β-cell responsivity in response to GLP-1 infusion. CONCLUSIONS: Variation in GLP1R may alter insulin secretion in response to exogenous GLP-1. Future studies will determine whether such variation accounts for interindividual differences in response to GLP-1–based therapy.